The Impact Assessment of the Mineral Aggregates’ Deposits on the Storage Area - Anca ȘERBAN; Adrian LEOPA (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
The construction sector is vital for our modern society such that most of the modern activities are dependent on constructions. The demographic increase and the longing of our times to better living conditions are the main exponents of unprecedented development in the construction field. The consequence of this phenomenon is the continuous growth of waste from construction and demolition. The management of these waste according to the sustainable development principles involves recycling or where not possible their storage considering the environmental tasks. This paper marks out the management of the two construction and demolition wastes, gas-formed concrete and concrete, taking account of the chemical composition of the leachate resulted from the waste drainage in the ground due to precipitation.